High-dose subconjunctival cyclosporine a implants do not affect corneal neovascularization after high-risk keratoplasty - Bock, Felix; Matthaei, Mario; Reinhard, Thomas; Böhringer, Daniel; Christoph, Jan; Ganslandt, Thomas; Cursiefen, Claus (Ophthalmology, 2014)
To test whether subconjunctival cyclosporine A (CsA) implants affect the incidence and the degree of corneal neovascularization occurring after penetrating keratoplasty.Prospective, randomized, multicenter, controlled phase 2/3 clinical trial. The study comprised 43 trial sites in Germany, India, and the United States.Enrolled patients (n = 97) were randomized to 1 of 3 groups: treatment group A (n = 36), treatment group B (n = 40), and the control group (n = 21).Patients from each group received either of 2 doses of subconjunctival CsA (group A, low-dose CsA; group B, high-dose CsA) or placebo (carrier only) implants at the time of high-risk penetrating keratoplasty.The incidence and degree of corneal neovascularization occurring after penetrating keratoplasty were evaluated in a substudy (LX201-01 study: NCT00447187). A web-based image upload system was developed. Standardized digital slit-lamp pictures were quantitatively and objectively evaluated using Cell^F morphometry software.No statistically significant difference in incidence and degree of corneal neovascularization developing after penetrating keratoplasty was found between treatment groups and placebo group. Mean corneal neovascularization area at week 52 (visit 12) was 2.32±1.79% in treatment group A versus placebo (2.79±2.11%; P = 0.45) and 2.74±2.22% in treatment group B versus placebo (2.79±2.11%; P = 0.94).High-dose subconjunctival CsA implants do not significantly affect corneal neovascularization after high-risk penetrating keratoplasty. This suggests that local CsA has negligible antiangiogenic effects in the human cornea, at least in the transplant setting.
EVALuna2:135